La caracterización glocal como estrategia comunitaria: Competencias pertinentes del gestor social del conocimiento - Figueroa Martínez, Ericka Jazmin (2018)
In the present project, the previous knowledge of the social manager of knowledge based on the regulations of the Institutions of Higher Education is defined, the representation of the same in the context of the locality as a relevant scenario that the teacher-manager needs to know, since the work is in situ, vital for the conjuncture of the work that it carries out in its approach to the community. The methodology is participatory, with a bibliographic design. The theoretical nuclei are: guidelines for thedesign of projects of social responsibility, regulations of functions of the managers of Social Knowledge Management, resource management, instructions for the management of reporting matrices and monitoring matrices and monitoring of the implementation of the projects in the practices of connection with the community. The perspective of the functions of the manager are intertwined with the substantive functions such as: Research, Social Knowledge Management and Postgraduate. The objective is to characterize the monitoring and monitoring functions of the social responsibility project manager as a linkage manager within the glocal functions, its perspective and projection being to carry out a relevant and participatory social work with the community.